Conflict and Insecurity in Balochistan : A report by Pak Institute for Peace Studies - Sajjad, Tariq M (A Narratives Publication Islamabad, 2012)
Balochistan, have posed serious threats to Pakistan's internal security and stability. Plagued by a number of insurgent, religious extremist and sectarian groups, the security landscape of Balochistan has become exceedingly complex over the last few year. The federal government has taken a number of steps in recent years. However, Baloch nationalists and insurgents continue to dismiss the government's overtures, calling them nothing more than deception and a continuation of policies of former military ruler Gen Pervaz Musharraf. This book explores the different perspectives of Balochistan's conflict, along with the possible solution.
Include bibliograpgy, appendices
Keywords: Pakistan--Balochistān -- Insurgency -- Nationalism -- Political violence